2019
DOI: 10.1016/j.niox.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibitors 1400W and L-NIO inhibit angiogenesis pathway of colorectal cancer

Abstract: Background: It has been widely accepted that angiogenesis plays fundamental roles in colorectal cancer development, and therapeutic targeting of this pathway has achieved promising outcome. Recent reports have highlighted the involvement of nitric oxide synthases (NOS) in the development of angiogenesis in cancer; however, the mechanism and therapeutic value of NOS inhibitors in colon cancer are largely unknown.Objective: In this study, we investigated the effects and mechanism of the NOS inhibitors 1400W and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Our recent study [64] confirmed that the blockage of iNOS or eNOS significantly inhibited CRC cell proliferation due to the reduced level of NO. Two NOS inhibitors, 1400 W and L-NIO, hindered the CRC cell growth and migration.…”
Section: W and L-niosupporting
confidence: 59%
“…Our recent study [64] confirmed that the blockage of iNOS or eNOS significantly inhibited CRC cell proliferation due to the reduced level of NO. Two NOS inhibitors, 1400 W and L-NIO, hindered the CRC cell growth and migration.…”
Section: W and L-niosupporting
confidence: 59%
“…In COAD, NOS3 expressed relatively high level in tumour tissues and cancer cell lines, and patients with higher NOS3 levels were diagnosed with a later tumour stage. This was consistent with the observation that L-NIO (a NOS3 inhibitor) inhibited cell growth and angiogenesis in colorectal cancer, and the anti-tumour effect of E7080 (lenvatinib) could be increased after combination with L-NIO in colorectal cancer (31,32). Although the analyses of NOS3 expression from the current TCGA data was not statistically relevant to the prognosis in COAD patients, Marisi et al found that the NOS3 expression level affected the progression-free survival and overall survival (OS) of metastatic colorectal cancer patients (9).…”
Section: Discussionsupporting
confidence: 90%
“…Another NOS3 inhibitor, N(G)-nitro-L-arginine methyl ester (L-NAME) was also reported to inhibit PAAD tumour growth (15). In addition, L-NIO could promote the anti-tumour effect of lenvatinib (31,32). The NOS3 level was signi cantly correlated with outcomes of bevacizumab-based chemotherapy in COAD (9,35).…”
Section: Discussionmentioning
confidence: 99%
“…S100B activity led to a significant increase of both VEGF and NO release from cultured cells, that paralleled a marked upregulation of VEGF receptors 1/2 and iNOS protein expression in the same experimental conditions. VEGF and NO are crucial components of the angiogenesis network since they synergistically promote a pro-angiogenic milieu in the colon [26,27]. Different evidence produced by our research group has been addressed in the attempt to clarify the role exerted by an increased S100B level and perpetuation of chronic inflammation in the gut mucosa.…”
Section: Discussionmentioning
confidence: 99%